El ánimo de apropiación como elemento del delito de hurto : reflexiones a partir del plenario "Schneider" - Dias, Leandro A. (2017)
The aim of this article is to analyse whether the crime of theft requires an additional subjective element, besides taking another person's property: the intent to steal. In order to achieve this goal, the author will analyse the arguments put forward in the Schneider case of the Appeals Chamber on Criminal Matters, in which the judges decided that the crime of theft does not require an additional subjective element. Specifically, the author will argue that the wrongfulness of theft presupposes intent to steal, because with such intent the author communicates a strong message of hostility towards the system of property rights. This message, however, is not present in cases in which the author takes another person's property with the intent to return the stolen thing.